Protective Effects of Puerarin against Aβ1–42-Induced Learning and Memory Impairments in Mice - Wu, Lidan; Tong, Tong; Wan, Shutong; Yan, Tingxu; Ren, Fangyi; Bi, Kaishun; Jia, Ying (Planta Medica, 2017)
Puerarin is a major isoflavone glycoside from the root of Pueraria lobata. It has been reported that puerarin can protect neurons from oxidative stress-induced apoptosis. Emerging evidence suggests that oxidative damage is associated with Aβ-induced neuronal death. In the current study, we evaluated the effect of puerarin on Alzheimerʼs disease induced by Aβ and explored the potential mechanisms underlying this effect. We found that the escape latency of the Morris water maze was decreased in groups treated with puerarin compared to the model group (p < 0.01). In addition, there were significant differences between treated groups and the model group mice in a Y-maze test (p < 0.01). Furthermore, puerarin recovered the levels of brain-derived neurotrophic factor, phosphorylated tau, malondialdehyde, acetylcholine esterase, glycogen synthase kinase-3beta, and the activity of superoxide dismutase to some extent in the hippocampus and cerebral cortex. Shrinkage of nuclei and swollen and eccentrically dispersed neuronal bodies were observed in the hippocampus of Aβ-treated mice. These data demonstrate that puerarin might protect against cognitive deficits, oxidative stress, and neurodegeneration induced by Aβ1–42.
Keywords: puerarin; Pueraria lobata; Fabaceae; Aβ1–42; Alzheimerʼs disease; cognitive impairment